RELATIONSHIP OF AGE, PARITY AND BIRTH WEIGHT WITH A RUPTURE OF THE PERINEUM OF MATERNAL AT PMB - haria, paula; Wigati, Putri Wahyu; Saidah, Halimatus (Jurnal Mahasiswa Kesehatan, 2021)
Maternal Mortality Rate is one indicator of the quality of maternal health services in a country. Preliminary study at PMB Ny. "E" with the documentation method, from 45 mothers giving birth 35 (77.7%) ruptured perineum, 10 (22.2%) did not rupture, 25 spontaneous ruptures (71.4%), ruptured with episiotomy 10 (28.5 %). The purpose of the study was to analyze the relationship between age, parity and birth weight of babies with perineal rupture in women giving birth at PMB Ny. "E" Mojoroto District, Kediri City in 2020.The research design is correlational analytic with a cross sectional approach, a total sample of 66 respondents is sampling, the data is collected through a data collection sheet. The independent variables are age, parity and birth weight of the baby. dependent variable of perineal rupture. Bivariate analysis with Spearman Rho test.Spearman Rho correlation test age p value = 0.001 < 0.05, meaning that there is a relationship between age and perineal rupture. Parity p value = 0.007 < 0.05, meaning that there is a relationship between parity and perineal rupture. Birth weight p value = 0.007 < 0.05, meaning that there is a relationship between birth weight and perineal rupture. Conclusion: There is a relationship between age and perineal rupture. There is a relationship between parity and perineal rupture. There is a relationship between birth weight and perineal rupture.